Immune Checkpoint Function of CD85j in CD8 T Cell Differentiation and Aging - Gustafson, Claire E.; Qi, Qian; Hutter-Saunders, Jessica; Gupta, Sheena; Jadhav, Rohit; Newell, Evan; Maecker, Holden; Weyand, Cornelia M.; Goronzy, Jörg J. (Frontiers in Immunology, 2017)
Aging is associated with an increased susceptibility to infection and a failure to control latent viruses, that is thought to be driven, at least in part, by alterations in CD8 T cell function. The aging T cell repertoire is characterized by an accumulation of effector CD8 T cells, many of which express the negative regulatory receptor CD85j. To define the biological significance of CD85j expression on CD8 T cells and to address the question whether presence of CD85j in older individuals is beneficial or detrimental for immune function, we examined the specific attributes of CD8 T cells expressing CD85j as well as the functional role of CD85j in antigen-specific CD8 T cell responses during immune aging. Here, we show that CD85j is mainly expressed by terminally differentiated effector (TEMRAs) CD8 T cells, which increase with age, in CMV infection and in males. CD85j+ CMV-specific cells demonstrate clonal expansion. However, TCR diversity is similar between CD85j+ and CD85j- compartments, suggesting that CD85j does not directly impact the repertoire of antigen-specific cells. Further phenotypic and functional analyses revealed that CD85j identifies a specific subset of CMV-responsive CD8 T cells that co-express a marker of senescence (CD57) but retain poly-functional cytokine production and expression of cytotoxic mediators. Blocking CD85j binding enhanced proliferation of CMV-specific CD8 T cells upon antigen stimulation but did not alter polyfunctional cytokine production. Taken together, these data demonstrate that CD85j characterizes a population of “senescent”, but not exhausted antigen-specific effector CD8 T cells and indicates that CD85j is an important checkpoint regulator controlling expansion of virus-specific T cells during aging. Inhibition of CD85j activity may be a mechanism to promote stronger CD8 T cell effector responses during immune aging.